1994
DOI: 10.1002/ijch.199400007
|View full text |Cite
|
Sign up to set email alerts
|

Photofragment Translational Spectroscopy of Fluorinated Halomethanes

Abstract: The primary and secondary dissociation processes of CF2Br2 and CF2BrI have been studied by photofragment translational spectroscopy in a pulsed molecular beam. The photolysis of CF2Br2 at 193 nm produces mainly the fragment pair CF2Br + Br and, in a competing primary process, CF2 + Br2. The CF2Br radicals are formed with sufficient internal energy to overcome the barrier of the unimolecular secondary dissociation to CF2+ Br. The photodissociation of CF2BrI at 248 nm also proceeds along two decay pathways invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Also, no broad band feature appeared in the spectrum for wavenumbers higher than 700 cm −1 , due to the luminescence present when the number of layers decreased [46], indicating the presence of multilayer MoS2 flakes in our sample, as expected [47]. 2g , A 1g and E 2 2g (not seen in Figure 3) are a result of vibrational modes within the MoS 2 layer [43]. The E 1 2g and A 1g modes of the exfoliated MoS 2 nanosheets were centered at 379 cm −1 and 404 cm −1 , respectively [44].…”
Section: Femtosecond Laser Micromachining and Characterizationsupporting
confidence: 52%
See 1 more Smart Citation
“…Also, no broad band feature appeared in the spectrum for wavenumbers higher than 700 cm −1 , due to the luminescence present when the number of layers decreased [46], indicating the presence of multilayer MoS2 flakes in our sample, as expected [47]. 2g , A 1g and E 2 2g (not seen in Figure 3) are a result of vibrational modes within the MoS 2 layer [43]. The E 1 2g and A 1g modes of the exfoliated MoS 2 nanosheets were centered at 379 cm −1 and 404 cm −1 , respectively [44].…”
Section: Femtosecond Laser Micromachining and Characterizationsupporting
confidence: 52%
“…The sample was excited with laser light at 633 nm (1.96 eV), which closely matches the energy of the direct bandgap of MoS2 at room temperature [42]. Four first-order Raman active modes dominate the resonant Raman spectrum of MoS2, in which E1g, E 1 2g, A1g and E 2 2g (not seen in Figure 3) are a result of vibrational modes within the MoS2 layer [43]. The E 1 2g and A1g modes of the exfoliated MoS2 nanosheets were centered at 379 cm −1 and 404 cm −1 , respectively [44].…”
Section: Femtosecond Laser Micromachining and Characterizationmentioning
confidence: 99%
“…Photodissociation studies of CF 2 Br 2 have been performed at 193 and 248 nm using the rotatable mass spectrometric technique. 4,5 The radical channel was the only observed primary photodissociation channel in the 248-nm photolysis experiments, while both the radical and the molecular elimination channels were observed at 193 nm. The bromine atom product quantum yield obtained by fluorescence detection at 222 nm has been found to be 1.63, suggesting the presence of three-body dissociation channel after excitation in the center of the A-band.…”
Section: Introductionmentioning
confidence: 94%
“…Three primary channels, i.e., radical (R1), molecular elimination (R2), and three-body dissociation channels (R3), are attainable energetically in the A-band. [3][4][5][6][7][8][9][10][11] The CF 2 Br radical formed through the radical channel can undergo further photodissociation (R4) or unimolecular decay of internally hot radicals (R5).…”
Section: Introductionmentioning
confidence: 99%
“…This was first shown for photolysis at 193 nm in a molecular beam by Huber and co-workers. 17 Later, in ion imaging experiments, Park et al 8 reported a "trace" amount of Br 2 photoproduct following excitation at 234 nm. More recently, Lin and co-workers 5 probed Br 2 directly using cavity ring down spectroscopy, and reported a quantum yield of 0.04 for the molecular channel at 248 nm.…”
Section: Introductionmentioning
confidence: 99%